2014
DOI: 10.1179/1362171814y.0000000225
|View full text |Cite
|
Sign up to set email alerts
|

Real time monitoring of laser beam welding keyhole depth by laser interferometry

Abstract: The utility of a new laser interferometric technique, inline coherent imaging, for real time keyhole depth measurement during laser welding is demonstrated on five important engineering alloys. The keyhole depth was measured at 200 kHz with a spatial resolution of 22 mm using a probe beam, which enters the keyhole coaxially with the process beam. Keyhole fluctuations limited average weld depth determination to a resolution on the order of 100 mm. Real time keyhole depth data are compared with the weld depths m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…The ICI signature observed in this processing regime is consistent with ICI measurements taken of bead-on-plate laser keyhole welding processes (Blecher et al, 2014). The existence of a vapor channel during processing allows imaging beam penetration below the substrate level and subsequent measurement of keyhole depth.…”
Section: Varying Process Power Regimessupporting
confidence: 75%
See 1 more Smart Citation
“…The ICI signature observed in this processing regime is consistent with ICI measurements taken of bead-on-plate laser keyhole welding processes (Blecher et al, 2014). The existence of a vapor channel during processing allows imaging beam penetration below the substrate level and subsequent measurement of keyhole depth.…”
Section: Varying Process Power Regimessupporting
confidence: 75%
“…Work by Blecher et al (2014) demonstrated the ability of ICI to measure laser keyhole depths in a range of metals, including DH36 steel, 304 stainless steel, Inconel 690, Ti-6Al-4V, and 2219 aluminum alloy. Webster et al (2014) exploited the utility of ICI for feedback control in high-power laser welding applications.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for the joining of complex components, traditional fusion welding techniques still hold considerable importance [1,2], as these processing routes allow for reasonable joint integrity. Fusion welding processes include the older-type arc-welding methods such as TIG, MIG and laser-arc hybrid welding [3][4][5], and newer beam-welding methods such as laser and electron-beam [6]. The beam processes enable the heat source to become more focused, allowing the molten pool region to form a narrower, deeper weld.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, OCT was successfully used for welding quality control particularly for online high speed profiling of keyhole depth [4]. By implementing the principles and algorithms of the WELDEYE software platform, optimally adapted to the OCT system, fast and exact estimation of the welding location, the maximum keyhole depth which gives an evidence about the power of the processing laser, and the detection of the quality of the resulted weld are possible.…”
Section: Application Of Oct For Laser Welding Processesmentioning
confidence: 99%